The age of magic - Ben Okri (Head of Zeus, 2014)
'The Age of Magic has begun. Unveil your eyes.' Eight weary film-makers, travelling from Paris to Basel, arrive at a small Swiss hotel on the shores of a luminous lake. Above them, strewn with lights that twinkle in the darkness, looms the towering Rigi mountain. Over the course of three days and two nights, the travellers will find themselves drawn in to the mystery of the mountain reflected in the lake. One by one, they will be disturbed, enlightened, and transformed, each in a different way. An intoxicating and dreamlike tale unfolds. Allow yourself to be transformed.